The construction of a critical thinking about gender roles through children's litterature. Analysis of an action research process with children of 5 years - Sanjuán Álvarez, Marta; Ballarín Artigas, María (Ondina - Ondine, 2020)
This paper describes an intervention and research design in a third grade classroom for Early Childhood Education, aimed at stimulating critical thinking about gender roles. The design includes a previous questionnaire to know the original beliefs of the participants, and several sessions of reading and literary conversation. The selected works represent different ideological positions and literary treatments of male and female characters, and cover a very long lapse of time, in order to promote comparison and critical thought from a social perspective over time. The results show that the boys and girls of Early Childhood Education already have stereotyped gender ideas. However, the discussion and guided analysis of literary works have led them to question their stereotypes. This confirms the value of children’s literature in the construction of individual and social identity, the critical perception of reality and the development of reflexive ethical schemes from early childhood, whenever a critical reading reception is stimulated.Key words: children’s literature and gender roles, literature and construction of identity, reading responses, literary conversation, literature in Early Childhood Education